RELATIONSHIP OF CHALLENGES, RECOGNITION AND CO-WORKERS TO JOB SATISFACTION (STUDY OF HUMAN RESOURCE MANAGEMENT LITERATURE) - Niu Haitao (Dinasti International Journal of Digital Business Management, 2022)
The Literature Review article on the Relationship of Challenges, Recognition and Coworkers to Job Satisfaction is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research, within the scope of Human Resource Management. The method of writing this Literature Review article is using the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this study are: 1) Challenges related to job satisfaction; 2) Recognition related to Job Satisfaction; and 3) Colleagues related to Job Satisfaction. Apart from these 3 exogenous variables that affect the endogenous variable Job Satisfaction there are still many other factors including the variables of Salary, Work Environment and Workload.